Community Learning Center Efforts to Improve Information Literacy in the Community for Cyber Crime Prevention during a Pandemic - Nurhayati, Sri; Musa, Safuri; Boriboon, Gumpanat; Nuraeni, Rina; Putri, Shindriani (Journal of Nonformal Education, 2021)
This study explores the community learning centers' effort in improving the community's information literacy to prevent cybercrime during the pandemic era through an empirical examination of the phenomenon of pandemic COVID 19 social impacts in the specific context of Indonesia. The study used a simple research design approach with the case study method. The subject of this study consisted of five Community Learning Center’s managers from Cimahi District (CLC Nurul Islam Al Husna), Garut District (CLC Ngejah), East Jakarta District (CLC Faradika), and Karawang District (CLC Ash Sholahiyah and CLC Sanggar Juang), and two community education experts from Indonesia. Data were analyzed using triangulation, including extensive interviews from five community learning center's managers, interviews with community education experts, as well as secondary data. The study found that community learning center's efforts consist of conducting virtual socialization and also mentoring the community on information literacy, revitalizing parenting education on guiding children during their screen time, activating community reading center to create a lively discussion, and fostering community's critical thinking and information assessment. The contribution of this study to the literature on community education consists of presenting empirical evidence on the real contribution of Community Learning Center in improving the community's information literacy level while preventing the wide spreading of cyber-crime during the pandemic COVID 19 era.